Implementation of Caring For the Environment Green School in North Aceh District – Indonesia (Sumatra Journal of Disaster, Geography and Geography Education, 2023)
This study examines the implementation of the green school environmental care program. This type of research is survey research using a quantitative approach. The sampling technique used a purposive technique totaling 27 public elementary schools in North Aceh district. The data collection tool uses a questionnaire. Data collection techniques using observation, interviews, documentation. Data analysis techniques using percentage analysis. The results showed that the implementation of green schools in North Aceh District was in good category (81%). This means that the school has implemented the green school environmental care program well to create a clean and comfortable school environment as a place for learning process activities to take place